INFORMATION SKILLS: PERSPECTIVES AND ALTERNATIVES IN SEARCH STRATEGIES - Salim, Juhana; Ming, Ding Choo (Malaysian Journal of Library and Information Science, 2004)
This article points out the ability of information technology to generate, process and disseminate information, which expands faster than our capability to access, receive, filter, accept, integrate, manage and use information. As a result we are faced with information overload. On the other hand, in performing daily work routines, only relevant information is needed. To acquire the needed information, having skills in strategizing information searches is one of the criteria of an information literate person. The benefits obtained from innovative processes involving use of information are extensive. This article elaborates on how human resource managers can reap the benefits from the extensive use of information. Another aspect discussed in relation to information skills is language. Language command appears to be an important factor determining the precision of the information being searched. This is also because the relevance of the information that is being sought depends on the linguistic aspect, terms and concepts that are being used in indexing and searching. Information search is an activity that is performed to acquire relevant document. The success of searching relevant document depends on many factors. This article provides some basic techniques that can be used by means of term associations and also as a way to manage some of the problems involving language use. Hence, one can ensure that information searches conducted can be more effective and relevant. The author has developed a model to analyse information literacy concept and its relationship with research implementation process, which stresses on several elements of aspects of teaching specific information skills. Emphasis is given on integrating cognitive elements, thinking skills and strategies in the information research process.